NLO QCD+EW predictions for tHj and tZj production at the LHC - Davide Pagani; Ioannis Tsinikos; Eleni Vryonidou (Journal of High Energy Physics, 2020)
Abstract In this work we calculate the cross sections for the hadroproduction of a single top quark or antiquark in association with a Higgs (tHj) or Z boson (tZj) at NLO QCD+EW accuracy. In the case of tZj production we consider both the case of the Z boson undecayed and the complete final state tℓ + ℓ − j, including off-shell and non-resonant effects. We perform our calculation in the five-flavour-scheme (5FS), without selecting any specific production channel (s-, t- or tW associated). Moreover, we provide a more realistic estimate of the theory uncertainty by carefully including the differences between the four-flavour-scheme (4FS) and 5FS predictions. The difficulties underlying this procedure in the presence of EW corrections are discussed in detail. We find that NLO EW corrections are in general within the NLO QCD theory uncertainties only if the flavour scheme uncertainty (4FS vs. 5FS) is taken into account. For the case of tℓ + ℓ − j production we also investigate differences between NLO QCD+EW predictions and NLO QCD predictions matched with a parton shower simulation including multiple photon emissions.